THE RELATIONSHIP OF NUTRITIONAL STATUS WITH CRUDE MOTOR DEVELOPMENT IN CHILDREN AGED 2-3 YEARS IN POSYANDU WORK AREA SITU UDIK PUSKESMAS: HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK KASAR PADA ANAK USIA 2-3 TAHUN DI POSYANDU WILAYAH KERJA PUSKESMAS SITU UDIK - Dewi Dewi Nopitasari; Elpinaria Elpinaria Girsang; Reny Reny Siswanti (Jurnal Ilmiah Wijaya, 2019)
According to UNICEF in 2011,dataofthe high number ofgrowth and development disorderinchildren under fivewas obtained,especially motor development disorder where (27.5%) or 3 million children had disorder. This research aims to determine theCorrelation ofNutritional StatusandGross Motor Developmentin 2-3 Year OldChildren atMaternal and Child Health Servicein Situ UdikCommunity Health Center Working Area. This is an analytic researchwith cross-sectional research design. This research was conducted atMaternal and Child Health Service atSitu UdikCommunity Health CenterinOctober 2017-October 2018 with total sample of 114 2-3 year oldchildrenby implementingSlovin formula for the sampling. The instruments used weredemographic questionnaire, DDST IIobservation sheet, and weight scale that had been provided. Furthermore,univariate and bivariate analysis were applied in analyzing the data. Based on nutritional status,children who hadmalnutrition were 22 children (29.7%) with normal motor development, 43 children (58.1%) were suspected abnormal motor development, and 9 children (12.2%) who could not be tested. Children who hadgood nutrition were 21 children (56.8%) with normal gross motor development, 10 children (27.0%) were suspected, and 6 children (16.2%) who could not be tested. Children who hadovernutrition were 2 children (66.7%) with normal gross motor development, 1 (33.3%) child were suspected abnormal motor development. In addition, the statistical test value = 0.026 obtained meaning thatnutritional status has significant correlation withgross motor development in 2-3 year oldchildren atMaternal and Child Health Service in Situ Udik Community Health Center Working Area.